Adoption and Usage Intention of Consumers Towards Telemedicine Among People During Pandemic Times - Charu Saxena; Pardeep Kumar; Pratibha Thakur (ACHSM, 2022)
OBJECTIVE: As COVID-19 engulfed the world, people are shifting to a new way of life with social distancing and self isolation, especially in developing countries. In such a scenario, online retailing has gone through a sea change with a new wave of increased demand and where the healthcare sector has also adjusted with the augmented transition from physical shops to e-commerce. The current study aims to assess the adoption and usage intention of consumers towards telemedicine among people during pandemic times. METHOD: The adoption of telemedicine by consumers depends upon some factors such as reliability, affordability, convenience, authenticity, offers and discount; which could enhance the intention to adopt and continual use by consumers. A modified version of 'Technology Acceptance Model' is incorporated in this study to validate the concept of adoption of telemedicine in cities of North India. RESULTS: The study has found the positive and significant relationship between the factors of adoption and the intention to adopt telemedicine. Also, the 'Effect of COVID-19' plays a moderating role between the different factors of adoption and the intention to adopt telemedicine. CONCLUSION: The adoption of telemedicine by people is significantly associated with different internal and external factors. The intention to adopt telemedicine is the construct that strongly influences the actual usage of telemedicine in developing countries. The scope of this study is restricted to the Northern region of India. A future study can be undertaken in relation to the global perspective of consumers.